Informal economy in Tunisia - Hedhli Mayssa; Hadhek Zouhaier (Eximia, 2024)
Informality has been a phenomenon that has existed in Tunisia for a long time; it expanded with the Tunisian revolution. The relationship between informal economy and GDP varies in only one direction, that is to say only informality has a negative effect on growth...The expansion of the informal sector comes back to the problem of economic freedom, Tunisia is among the least economically free countries also the political institutional framework such as the problem of government efficiency, the high level of corruption and political instability are among the explanatory variables of informality.